Reações de maleinização do óleo de mamona na presença de iniciadores de radicais livres - Maia, Dayanne Lara Holanda (2016)
The maleate castor oil is used in drying oils, water-soluble paints, personal care products, synthetic lubricants, etc. Initially, maleate castor oil production was studied from of maleinization reaction between castor oil and maleic anhydride. Then, maleinization reactions of castor oil were carried out using benzoyl peroxide (BPO) and di-tert-butyl peroxide (DTBP) as reaction initiator to maleate castor oil production. Reactions were carried out in a batch-type reactor. The performance of the free-radical reaction was evaluated by comparing it with the reaction carried out in absence of initiator. The response surface methodology (RSM) was used to evaluate the influence of temperature and initiator concentration on castor oil conversion into maleate castor oil in the presence of BPO and DTBP. Analysis of operating conditions by RSM showed that the most significant variable the reaction was temperature, and that the initiator concentration had little significance on the conversion of castor oil. Maleate castor oil was characterized by FTIR and NMR spectroscopy. The best conversion obtained in maleinization reaction with BPO was 94.7%, at 120 °C and 176.6 °C, when initiator concentration was 0.010% in a reaction time of 180 min. The use of BPO and DTBP was most significant on increasing castor oil conversion in 30 min and 60 min reaction, respectively. After 90 min, the use of the initiator BPO and DTBP had little influence on increasing the conversion of castor oil. Besides, it was analyzed the influence of six initiators: benzoyl peroxide (BPO), di-tert-butyl peroxide (DTBP), dicumyl peroxide (DCP), tert-butyl peroxybenzoate (TBPB), sodium persulfate (PSNA) and potassium persulfate (PSK). The use of these initiators in the reaction has contributed to reduction of reaction time. The reduction was of approximately 30 min. Sodium persulfate was shown very promising in reaction at 140 °C to have reached 90% conversion in only 70 min, besides the initiator of lowest cost among the studied.